FACTORS ASSOCIATED WITH HEALTH PROMOTION BEHAVIOR OF THE ELDERLY IN BAN MAI SUB-DISTRICT, MUEANG DISTRICT, NAKHON RATCHASIMA PROVINCE - Praiwong, Chanyanutch (Primary Health Care Journal (Northeastern Edition), 2022)
The purpose of the descriptive research is to study factors associated with health promotion behavior of the elderly, Ban Mai sub-district, Mueang district, Nakhon Ratchasima province. The sample was 230 elderly by simple random sampling. The data was collected by questionnaire. The IOC was between 0.67-1.00 and Cronbach’s alpha coefficient of knowledge about fact health promotion behavior, and perceived ability in the self-health promotion were equal to 0.75 and 0.83. The data analysis used frequency, percentage, mean, standard deviation, the maximum score, and the minimum score, the Chi-Square test, and Pearson's product-moment correlation coefficient. The result of the research revealed that the most of the samples were female, 45.3%, the average age was 68.63 years old, graduated from primary school level 4 in 93.1%, the marital status was 65.2%, the average income was 1,566 baht per month, chronic disease was 43.5% and congenital disease was high blood pressure at the moderate level in 39.6%, followed by the low level and the high level was 33.0% and 3.9% respectively. The education level, monthly income, knowledge in health promotion, and perceived ability in health promotion had a relationship with the health behavior of the elderly with statistical significance (P-value <.05).